A Narrative Review to Identify Promising Approaches for Digital Health Interventions to Support Emotion Regulation for Adolescents With Attention-Deficit/Hyperactivity Disorder - Aja Louise Murray; Melissa Thye; Ingrid Obsuth; Shufang Cai; Michael Lui; Corina Orr; Anusha Saravanan (JMIR Mental Health)
Emotion regulation difficulties affect many adolescents with attention-deficit/hyperactivity disorder (ADHD), and previous research has highlighted a need for accessible interventions to support them in this domain, especially in real-life contexts. Digital health interventions (DHIs) can be embedded in adolescents’ daily lives and thus offer considerable promise for meeting this need. However, there is a lack of information to guide the development of suitable emotion regulation DHIs for this population. The goal of this study is, therefore, to identify recommendations to guide the development of emotion regulation DHIs for adolescents with ADHD. This narrative review synthesizes diverse relevant evidence to inform their development, including promising therapeutic approaches and components and relevant design and development considerations. We find that there is very little direct evidence of “what works” for emotion regulation DHIs and emotion regulation interventions more generally for adolescents with ADHD; however, we identify promising therapeutic approaches for new DHIs. We also recommend following a co-design or coproduction approach with adolescents with ADHD, including exploring elements designed to motivate and engage young people to support sustained adherence. We conclude that DHIs are a promising approach for emotion regulation interventions for adolescents with ADHD, could draw on a range of existing therapeutic approaches, and should be co-designed with users themselves.